Laparoscopic Sleeve Gastrectomy Versus Roux-Y-Gastric Bypass for Morbid Obesity—3-Year Outcomes of the Prospective Randomized Swiss Multicenter Bypass Or Sleeve Study (SM-BOSS). Issue 3 (March 2017) - Peterli, Ralph; Wölnerhanssen, Bettina Karin; Vetter, Diana; Nett, Philipp; Gass, Markus; Borbély, Yves; Peters, Thomas; Schiesser, Marc; Schultes, Bernd; Beglinger, Christoph; Drewe, Juergen; Bueter, Marco
Abstract : Objective: Laparoscopic sleeve gastrectomy (LSG) is performed almost as often in Europe as laparoscopic Roux-Y-Gastric Bypass (LRYGB). We present the 3-year interim results of the 5-year prospective, randomized trial comparing the 2 procedures (Swiss Multicentre Bypass Or Sleeve Study; SM-BOSS). Methods: Initially, 217 patients (LSG, n = 107; LRYGB, n = 110) were randomized to receive either LSG or LRYGB at 4 bariatric centers in Switzerland. Mean body mass index of all patients was 44 ± 11 kg/m 2, mean age was 43 ± 5.3 years, and 72% of patients were female. Minimal follow-up was 3 years with a rate of 97%. Both groups were compared for weight loss, comorbidities, quality of life, and complications. Results: Excessive body mass index loss was similar between LSG and LRYGB at each time point (1 year: 72.3 ± 21.9% vs. 76.6 ± 20.9%, P = 0.139; 2 years: 74.7 ± 29.8% vs. 77.7 ± 30%, P = 0.513; 3 years: 70.9 ± 23.8% vs. 73.8 ± 23.3%, P = 0.316). At this interim 3-year time point, comorbidities were significantly reduced and comparable after both procedures except for gastro-esophageal reflux disease and dyslipidemia, which were more successfully treated by LRYGB. Quality of life increased significantly in both groups after 1, 2, and 3 years postsurgery. There was no statistically significant difference in number of complications treated by reoperation (LSG, n = 9; LRYGB, n = 16, P = 0.15) or number of complications treated conservatively. Conclusions: In this trial, LSG and LRYGB are equally efficient regarding weight loss, quality of life, and complications up to 3 years postsurgery. Improvement of comorbidities is similar except for gastro-esophageal reflux disease and dyslipidemia that appear to be more successfully treated by LRYGB.